Engaging stakeholders in using future scenarios to analyse the potential impacts of agricultural development in the Lake Victoria Basin - United Nations Environment Programme World Conservation Monitoring Centre (2016)
This report presents the proceedings from the inception workshop for the project “Engaging stakeholders in using future scenarios to analyse the potential impacts of agricultural development in the Lake Victoria Basin”. This two-year project (2015-2017) aims to ensure that land-use related decision-making in the Lake Victoria Basin (LVB) takes into consideration biodiversity and ecosystem services and is based on sound information and on the consideration of trade-offs between food production and conservation goals. The long-term outcome of the project will be a reduction in the adverse impacts of agricultural commodity developments on biodiversity, ecosystem services and human well-being in the LVB.